Design and synthesis of N‐benzoyl amino acid derivatives as DNA methylation inhibitors. (24th June 2016) - Garella, Davide; Atlante, Sandra; Borretto, Emily; Cocco, Mattia; Giorgis, Marta; Costale, Annalisa; Stevanato, Livio; Miglio, Gianluca; Cencioni, Chiara; Fernández‐de Gortari, Eli; Medina‐Franco, José L.; Spallotta, Francesco; et al.
Abstract : The inhibition of human DNA Methyl Transferases (DNMT) is a novel promising approach to address the epigenetic dysregulation of gene expression in different diseases. Inspired by the validated virtual screening hit NSC137546, a series of N ‐benzoyl amino acid analogues was synthesized and obtained compounds were assessed for their ability to inhibit DNMT‐dependent DNA methylation in vitro . The biological screening allowed the definition of a set of preliminary structure–activity relationships and the identification of compounds promising for further development. Among the synthesized compounds, L ‐glutamic acid derivatives22, 23, and24 showed the highest ability to prevent DNA methylation in a total cell lysate. Compound22 inhibited DNMT1 and DNMT3A activity in a concentration‐dependent manner in the micromolar range. In addition, compound22 proved to be stable in human serum and it was thus selected as a starting point for further biological studies. Abstract : A series of N ‐benzoyl amino acid derivatives was synthesized by modulation of three different molecular moieties (A, B, and C). The ability of synthesized compounds to inhibit DNMT‐dependent total DNA methylation was evaluated. The most active compound22 inhibited both DNMT1‐ and DNMT3A‐mediated DNA methylation in a concentration‐dependent manner at micromolar concentration. Docking studies suggest putative binding at the substrate site of both DNMT isoforms studied.